Performance Based Budgeting System Design in Universitas Sebelas Maret (International Journal of Management and Sustainability, 2015)
Performance based budgeting requires information system in order to attain its goal. Universitas Sebelas Maret (UNS) has used the combination system of performance based budgeting and traditional budgeting. The objective of this research is to design application software that is useful for UNS in its budgeting process. This research analyzes system application of performance based budgeting. The system design consists of output design, document design, and input design. Output design of performance based budgeting consists of Planning Report, Financial Statement, and Performance Report. These reports supposed to be integrated. In document design, all files should be documented by the Development Plan Team. The final design is input design, which concern about planning and activities process.